The Role of the School Literacy Movement in Shaping Creative and Responsible Student Character in Pancasila Education Lessons at SMPN 1 Ciawigebang - Prasetiyani, Lani; Abdulkarim, Aim; Rahmat, Rahmat (Universitas Lambung Mangkurat, 2026)
Literacy mastery is an important foundation for developing superior, creative, and responsible human resources. However, various results from international and national studies indicate that literacy skills of students in Indonesia still face challenges, both in terms of reading interest, critical understanding, and character development. This research aims to analyze the planning, implementation, and success rate of the literacy movement in shaping creative and responsible student character in Pancasila Education subjects at SMP Negeri 1 Ciawigebang. This research uses a mixed methods approach with a sequential exploratory strategy, employing observation, interviews, documentation, and questionnaires. The results of the qualitative analysis research indicate that the school literacy movement plan has been implemented systematically and integrated with Pancasila Education, involving all school stakeholders. The implementation of school literacy movements through the stages of habituation, development, and learning is able to encourage active student involvement, enhance creativity, and foster a sense of responsibility. The success rate of the school literacy movement is not only measured by the final results, but also by the learning process experienced by students. Quantitative analysis reveals a strong and significant relationship between the school literacy movement and the development of students' creative and responsible character. Thus, the role of the school literacy movement, consistently integrated into Pancasila Education learning, is proven effective in shaping students' creative and responsible character, in line with the Pancasila Student Profile.